Tâhâ Abdurrahman'ın Modernite ve Modernist Kur'an Yorumlarına Yönelik Eleştirisi - (:unkn) unknown (My University, 2015)
0

This paper presents the views of Taha Abdurrahman, a contemporary Moroccan thinker, on the nature of a progressive understanding of the Qur'an and his criti- cism aimed at the modernist interpretations of the Qur'an as displayed in his Ruh al-hadasa. Thus the paper is based mainly on Ruh al-hadasa and uses a descriptive method in which Taha Abdurrahman's critiques and opinions on the topic are presented without much endeavor to analyze these views. The objective of this is to present Taha Abdurrahman's conception of progress and the Islamic model of renovation formulated by him to the Turkish academia where his works and opinions are not widely known. The paper also aims to encourage analytical and critical works on the views of Taha Abdurrahman in the Turkish language
Taha Abdurrahman's Criticism of Modernity and of the Modernist Interpretations of the Qur'an
Keywords: Din Bilimi